Hardening liquid and preparation method thereof, hardening film and vehicle-mounted display device

By modifying nanosol coated with infrared barriers and compounded with acrylate oligomers with waterproof groups, the problem of reduced adhesion of the hardened film in high temperature and high humidity environment is solved, and the high temperature and high humidity stability and thermal insulation performance of the hardened film are improved.

CN119775886APending Publication Date: 2025-04-08NINGBO HUGHSTAR ADVANCED MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411965080.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the high temperature and high humidity environment, the precipitation of the insulating additives leads to the reduction of adhesion of the hardened functional layer or even falling off.

Method used

Modified nanosol is used to coat infrared barriers and coordinate with acrylate oligomers with waterproof groups to form a hardened liquid to improve the high temperature and high humidity stability and thermal insulation performance of the hardened film.

Benefits of technology

It effectively avoids the precipitation of infrared barriers in high temperature and high humidity environments, enhances the adhesion of the hardened functional layer, improves the high and low temperature and high humidity stability of the hardened film, and has good heat insulation, salt spray resistance and optical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775886A_ABST
    Figure CN119775886A_ABST
Patent Text Reader

Abstract

The present application relates to a hardening liquid and a preparation method thereof, as well as a hardening film and a vehicle-mounted display device, and belongs to the technical field of hardening films. The hardening liquid includes an acrylate oligomer with a waterproof group, a diluting monomer and an infrared-proof material; wherein the infrared-proof material includes an infrared blocking agent coated with a modified nanosol, and the modified nanosol includes at least one of a nanosol modified by a silane coupling agent or a nanosol modified by an acrylate. By adding an infrared blocking agent coated with a modified nanosol to the hardening liquid, while achieving good thermal insulation performance of the hardened film, the hardened functional layer can be ensured to have good high-temperature and high-humidity stability and salt spray resistance; and the acrylate oligomer with a waterproof group has good water resistance after reaction, which can effectively improve the salt spray resistance of the hardened film, and further improve the high and low temperature and high temperature and high humidity stability of the hardened film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of hardened films, and in particular to a hardening liquid and a preparation method thereof, as well as a hardened film and a vehicle-mounted display device. Background Art

[0002] The hardened film usually includes a base film and a hardened functional layer attached to the surface of the base film. It uses the photosensitivity of the photoinitiator to polymerize, graft or crosslink unsaturated organic matter under ultraviolet light to form a film. Because of its good resistance to high temperature and moisture, it has been widely used as a protective film for outdoor display screens, vehicle-mounted display screens, outdoor lamps, etc. When used in vehicle-mounted display screens, since they are often set in a closed space outdoors, the hardened film must also have certain heat insulation properties. However, if heat insulation additives (such as nano tungsten oxide, tin oxide, etc.) are directly added to the hardening liquid, water vapor will penetrate into the hardened functional layer in a high temperature and high humidity environment, and the heat insulation additives will precipitate, which will cause the adhesion of the hardened functional layer to decrease or even fall off. Summary of the invention

[0003] In order to solve the above-mentioned technical problems, the purpose of this application includes providing a hardening liquid and a preparation method thereof, as well as a hardening film and a vehicle-mounted display device, which can give the hardening film good thermal insulation properties while ensuring that the hardening functional layer has good high temperature and high humidity stability.

[0004] In a first aspect, the present application provides a hardening liquid comprising an acrylate oligomer having a waterproof group, a diluent monomer and an infrared-proof material; wherein the infrared-proof material comprises an infrared blocking agent coated with a modified nanosol, and the modified nanosol comprises at least one of a nanosol modified by a silane coupling agent or a nanosol modified by an acrylate.

[0005] In the above technical scheme, by adding anti-infrared material to the curing liquid, the hardened film can be given good heat insulation performance. In addition, by using modified nanosol to coat the infrared blocking agent, the modified nanosol can participate in the photocuring cross-linking reaction of the subsequent hardening functional layer, thereby enhancing the interface bonding force between the infrared blocking agent and the hardening functional layer as a whole, effectively avoiding the precipitation problem of the infrared blocking agent under high temperature and high humidity environment, and then enhancing the adhesion of the hardening functional layer, and at the same time, it can also solve the warping problem that may occur in the hardened film under high temperature conditions. In addition, by using an acrylate oligomer with a waterproof group as the main resin, it has good water resistance after the photocuring reaction, which can effectively improve the salt spray resistance of the hardened film, and further improve the high and low temperature and high temperature and high humidity stability of the hardened film. In this application, by using an acrylate oligomer with a waterproof group and a modified nanosol coated infrared blocking agent, the hardened film has good high temperature and high humidity stability, heat insulation, high temperature resistance, salt spray resistance and optical properties (such as transmittance and haze) at the same time.

[0006] In some embodiments, the infrared blocking agent includes at least one of tin oxide, tungsten oxide, antimony tin oxide, or indium antimony oxide; and the particle size of the infrared blocking agent is 10 to 100 nm.

[0007] In the above technical solution, by controlling the type and particle size of the infrared blocking agent, the infrared blocking agent wrapped by the nanosol can have good heat insulation performance and is not easy to precipitate after being coated with the modified nanosol.

[0008] In some embodiments, the nanosol includes at least one of silica sol, aluminum sol or zirconium sol; the silane coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane or allyltrimethylsilane; the acrylate includes at least one of polyacrylate and acrylate monomer.

[0009] In the above technical scheme, by selecting the nanosol, and the types of silane coupling agent and acrylate used for modification, the modified nanosol has good compatibility with the resin and can participate in the photocuring reaction, thereby improving the high temperature and high humidity stability and salt spray resistance of the hardened film.

[0010] In some embodiments, the modified nanosol includes a first modified sol and a second modified sol, the infrared blocking agent is located on the surface of the first modified sol, and the second modified sol covers the first modified sol and the infrared blocking agent.

[0011] In the above technical scheme, by using the first modified sol and the second modified sol to treat the infrared blocking agent, the infrared blocking agent can be effectively encapsulated and isolated, which can further prevent the infrared blocking agent from precipitating in a high temperature and high humidity environment, and can further enhance the interface bonding strength between the anti-infrared material and the hardened functional layer.

[0012] In some embodiments, the acrylate oligomer having a water-repellent group includes at least one of a polyether-modified polyurethane acrylic resin or a polycarbonate-modified polyurethane acrylic resin. The above-mentioned acrylate oligomer having a water-repellent group has good water resistance after the photocuring reaction, and can effectively improve the salt spray resistance and high temperature and high temperature and high humidity stability of the hardened film.

[0013] In some embodiments, the diluent monomer includes an acrylate monomer. The use of acrylate compounds in both the diluent monomer and the main resin can improve the curing and cross-linking effect of the hardening solution, thereby further improving various properties of the hardened film.

[0014] In some embodiments, the curing liquid includes the following components by weight: 5 to 30 parts of an acrylate oligomer having a waterproof group, 2 to 8 parts of a diluent monomer, 1 to 6 parts of an infrared-proof material, 0.5 to 3 parts of an initiator, and 50 to 140 parts of a dispersing solvent. By controlling the appropriate ratio of each component, the light-curing cross-linking effect of the curing liquid can be improved, thereby further improving the comprehensive performance of the cured film.

[0015] In a second aspect, the present application provides a method for preparing the above-mentioned hardening liquid, comprising the following steps:

[0016] The first modified sol is mixed with an infrared blocking agent to obtain a first system; the first system is mixed with a second modified sol, an alcohol solvent and polyether siloxane to obtain an infrared protection material; wherein the first modified sol and the second modified sol each independently include at least one of a silane coupling agent modified nanosol or an acrylate modified nanosol;

[0017] An acrylate oligomer having a water-repellent group, a diluent monomer, an infrared-proof material, an initiator and a dispersing solvent are mixed to obtain a hardening solution.

[0018] Existing research has disclosed that the infrared blocking agent is directly added to the hardening liquid. Although it can also play a certain heat insulation role, since the infrared blocking agent does not participate in the subsequent UV curing reaction, the infrared blocking agent will precipitate under high temperature and high humidity environment, thereby reducing the adhesion of the hardening functional layer or even falling off. In this application, by using modified nanosol to coat the infrared blocking agent, the first modified sol can first effectively adsorb the infrared blocking agent on the surface, and then the alcohol solvent and polyether siloxane can make the second modified sol agglomerate and wrap the surface of the first modified sol adsorbed with the infrared blocking agent on the surface, so that the infrared blocking agent is effectively encapsulated. Then the infrared-proof material is mixed with components such as acrylic oligomers and diluent monomers with waterproof groups to obtain a hardening liquid. The preparation method is simple to operate and suitable for mass production. Since the modified nanosol has good compatibility with the resin system and can participate in the UV curing reaction later, it has good high temperature and high humidity stability while giving the hardened film heat insulation performance, and can avoid the precipitation of infrared blocking agents to reduce the adhesion of the hardening functional layer. Furthermore, since the acrylate oligomers having waterproof groups have good water resistance after the photocuring reaction, the salt spray resistance of the hardened film can be effectively improved after curing and cross-linking.

[0019] In some embodiments, the mass ratio of the first modified sol to the infrared blocking agent is (5-10):1; the mass ratio of the second modified sol to the infrared blocking agent is (5-40):1.

[0020] In the above technical solution, the encapsulation effect of the infrared blocking agent can be further improved by controlling the dosage of the first modified sol, the second modified sol and the infrared blocking agent.

[0021] In a third aspect, the present application provides a hardened film, including a base film and a hardened functional layer attached to the surface of the base film, wherein the hardened functional layer is obtained by coating and photocuring the above-mentioned hardening liquid.

[0022] The hardened film in the present application has a hardened functional layer obtained by photocuring the above-mentioned hardening liquid, has good thermal insulation performance, and also has good high temperature and high humidity stability, high temperature resistance, salt spray resistance and optical properties (such as transmittance and haze).

[0023] In a fourth aspect, the present application provides a vehicle-mounted display device, comprising the above-mentioned hardened film. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is a process flow chart of the method for preparing the hardening liquid provided in an embodiment of the present application.

[0026] Figure 2 This is a curve chart of the thermal insulation test results of the hardened film provided in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0027] Hardened film is widely used as a protective film for outdoor display screens, vehicle-mounted display screens, outdoor lamps, etc. When applied to vehicle-mounted display screens, since they are often placed in a closed space outdoors, the hardened film must also have certain heat insulation properties. However, if heat insulation additives (such as nano tungsten oxide, tin oxide, etc.) are directly added to the hardened functional layer, water vapor will penetrate into the hardened functional layer in a high temperature and high humidity environment, and the heat insulation additives will precipitate, which will cause the adhesion of the hardened functional layer to decrease or even fall off.

[0028] Based on this, the present application provides a hardening liquid, including an acrylate oligomer with a waterproof group, a diluent monomer and an infrared-proof material; wherein the infrared-proof material includes an infrared blocking agent coated with a modified nanosol, and the modified nanosol includes at least one of a nanosol modified by a silane coupling agent or a nanosol modified by an acrylate.

[0029] By adding anti-infrared material to the curing liquid, the hardened film can be given good thermal insulation performance. In addition, by using modified nanosol to coat the infrared blocking agent, the modified nanosol can subsequently participate in the photocuring reaction of the hardened functional layer. After being wrapped, it can effectively avoid the precipitation problem of the infrared blocking agent under high temperature and high humidity environment, so that the hardened functional layer has good adhesion, and the warping problem that may occur in the hardened film under high temperature conditions can also be solved. In addition, by using acrylate oligomers with waterproof groups as the main resin, it has good water resistance after the photocuring reaction, which can effectively improve the salt spray resistance of the hardened film, and further improve the high and low temperature and high temperature and high humidity stability of the hardened film. In this application, by using acrylate oligomers with waterproof groups, diluting monomers and modified nanosol coated infrared blocking agents, the hardened film has good thermal insulation performance, and has good high temperature and high humidity stability, salt spray resistance, high temperature resistance and optical properties (such as transmittance and haze).

[0030] Figure 1 This is a process flow chart of a method for preparing a hardening liquid provided in an embodiment of the present application. Figure 1 The preparation method of the hardening solution comprises the following steps:

[0031] S110, mixing the first modified sol with an infrared blocking agent to obtain a first system; mixing the first system with a second modified sol, an alcohol solvent and polyether siloxane to obtain an infrared protection material; wherein the first modified sol and the second modified sol each independently include at least one of a silane coupling agent modified nanosol or an acrylate modified nanosol.

[0032] In some embodiments, the infrared blocker includes at least one of tin oxide, tungsten oxide, antimony tin oxide or indium antimony oxide, and the infrared blocking band of these infrared blockers is 700-2500nm; the particle size of the infrared blocker is 10-100nm, for example, 20nm, 50nm, etc.

[0033] In some embodiments, the nanosol includes at least one of silica sol, alumina sol, or zirconium sol.

[0034] In some embodiments, the silane coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, or allyltrimethylsilane.

[0035] In some embodiments, the acrylate includes at least one of polyacrylate and acrylate monomer. As an example, the polyacrylate may be at least one of polyurethane acrylate, silicone acrylate, or polyester acrylate; the acrylate monomer may be at least one of pentaerythritol hexaacrylate, pentaerythritol triacrylate, ethoxyethyl acrylate, trimethylolpropane triacrylate, hexanediol diacrylate, hexanediol diacrylate, isobornyl acrylate, trimethylolpropane trimethacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, trimethylolpropane triacrylate, dipentaerythritol hexaacrylate, dipentaerythritol pentaacrylate, or triisocyanuric acid triacrylate.

[0036] It should be noted that the modified nanosol used in the embodiments of the present application can be a commercially available product purchased directly, for example, the nanosol modified by a silane coupling agent can be MIBK-AC-2140Z (Nissan Chemical), SAL40-25 / 1 (Delixin), etc.; the nanosol modified by an acrylate can be NANOCRYL A215 (Evonik), etc.

[0037] In other embodiments, the modified nanosol used in the embodiments of the present application can also be self-made. As an example, the preparation method of the nanosol modified by a silane coupling agent may include the following steps: heating and stirring the silica sol and the silane coupling agent to react (for example, reacting at 65°C for 5 hours); then adding an appropriate amount of a basic compound (for example, triethylamine and 2-butanone), continuing to heat and stir the reaction for a period of time (for example, reacting at 65°C for 1 hour); finally, adding a cation exchange resin, stirring at room temperature for a period of time, filtering and removing the cation exchange resin, and obtaining a nanosol modified by a silane coupling agent.

[0038] In the embodiment of the present application, the infrared blocking agent is located on the surface of the first modified sol, and the second modified sol covers the first modified sol and the infrared blocking agent. It can be understood that the first modified sol and the second modified sol can be independently selected from at least one of modified silica sol, modified aluminum sol or modified zirconium sol.

[0039] In some embodiments, the mass ratio of the first modified sol to the infrared blocking agent is (5-10): 1, and the mass ratio of the second modified sol to the infrared blocking agent is (5-40): 1. As an example, the mass ratio of the first modified sol to the infrared blocking agent can be 5: 1, 10: 1, etc.; the mass ratio of the second modified sol to the infrared blocking agent can be 10: 1, 20: 1, 40: 1, etc.

[0040] The alcohol solvent may be at least one of isopropanol, propylene glycol and cyclopentanol; the mass ratio of the alcohol solvent to the infrared blocking agent is (3-100):1, such as 10:1, 20:1, 50:1, etc. The polyether siloxane may be at least one of polyether-modified polydimethylsiloxane and polyether-modified heptamethyltrisiloxane; the mass ratio of the polyether siloxane to the infrared blocking agent is (0.01-0.1):1, such as 0.02:1, 0.05:1, 0.1:1, etc.

[0041] By controlling the type and amount of the alcohol solvent and the polyether siloxane, the agglomeration of the second modified sol can be promoted, thereby further improving the encapsulation effect of the infrared blocking agent.

[0042] S120, mixing an acrylate oligomer having a water-repellent group, a diluent monomer, an infrared-proof material, an initiator, and a dispersing solvent to obtain a hardening solution.

[0043] In some embodiments, the components of the hardening liquid include, by weight: 5 to 30 parts of an acrylate oligomer having a waterproof group, 2 to 8 parts of a diluent monomer, 1 to 6 parts of an infrared-proof material, 0.5 to 3 parts of an initiator, and 50 to 140 parts of a dispersing solvent.

[0044] As an example, in the hardening liquid, the added amount of acrylic oligomers with waterproof groups is 5 parts, 10 parts, 20 parts, 30 parts, etc.; the added amount of diluent monomers is 2 parts, 4 parts, 5 parts, 7 parts, 8 parts, etc.; the added amount of infrared protection materials is 1 part, 2.5 parts, 3.5 parts, 5 parts, 6 parts, etc.; the added amount of initiators is 0.5 parts, 1 part, 1.6 parts, 2 parts, 3 parts, etc.; the added amount of dispersing solvents is 50 parts, 60 parts, 100 parts, 140 parts, etc.

[0045] In some embodiments, the acrylate oligomer having a water-repellent group may be selected from at least one of a polyether-modified polyurethane acrylic resin or a polycarbonate-modified polyurethane acrylic resin.

[0046] In some embodiments, the diluent monomer may be an acrylate monomer. By way of example, the diluent monomer may be at least one of pentaerythritol hexaacrylate, pentaerythritol triacrylate, ethoxyethyl acrylate, trimethylolpropane triacrylate, hexanediol diacrylate, hexanediol diacrylate, isobornyl acrylate, trimethylolpropane trimethacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, trimethylolpropane triacrylate, dipentaerythritol hexaacrylate, dipentaerythritol pentaacrylate, or triisocyanuric acid triacrylate.

[0047] Preferably, the diluent monomer is a multifunctional acrylate monomer, such as pentaerythritol hexaacrylate, dipentaerythritol hexaacrylate, and the like.

[0048] In some embodiments, the initiator includes at least one of a cleavage initiator or a hydrogen abstraction initiator. Optionally, the cleavage initiator includes at least one of 2-hydroxy-2-methylpropiophenone (1173), 1-hydroxycyclohexyl phenyl ketone (184), 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone (907), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl) butanone (369), and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (819). The hydrogen abstraction initiator includes at least one of benzophenone (BP), 4-methylbenzophenone, and 2,4,6-trimethylbenzophenone.

[0049] In some embodiments, the dispersing solvent includes at least one of an alcohol solvent, a ketone solvent, an ester solvent, a benzene solvent, and an ether solvent; wherein the alcohol solvent is at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol and isobutanol; the ketone solvent is at least one of acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone; the ester solvent is at least one of methyl acetate, ethyl acetate, propyl acetate and butyl acetate; the benzene solvent is at least one of toluene and xylene; the ether solvent is at least one of propylene glycol methyl ether and dipropylene glycol methyl ether.

[0050] In the above-mentioned preparation method, the present application first coats the infrared blocking agent with a modified nanosol, and then mixes it with components such as an acrylate oligomer having a waterproof group and a diluent monomer to obtain a hardening solution. The preparation method is simple to operate and suitable for mass production. Since the modified nanosol has good compatibility with the resin system and can participate in the UV curing reaction, while giving the hardened film thermal insulation properties, it also has good high-temperature and high-humidity stability, which can prevent the precipitation of the infrared blocking agent from reducing the adhesion of the hardened functional layer. In addition, the acrylate oligomer having a waterproof group and the anti-infrared material work synergistically, so that the hardened film can have good salt spray resistance.

[0051] The embodiment of the present application also provides a hardened film, including a base film and a hardened functional layer attached to the surface of the base film, and the hardened functional layer is obtained by coating and photocuring the above-mentioned hardening liquid.

[0052] In some embodiments, the method for preparing a hardened film may include the following steps: applying the hardening liquid to the surface of the base film, and performing ultraviolet light curing after drying to form a hardened functional layer to obtain a hardened film.

[0053] The base film may be made of at least one of polycarbonate (PC), polyethylene terephthalate (PET) or polymethyl methacrylate (PMMA). Preferably, the base film is made of PC.

[0054] The thickness of the base film can be 25-500 μm, preferably 25-125 μm; the thickness of the hardened functional layer is 2-6 μm. As an example, the thickness of the base film is 38 μm, 40 μm, 50 μm, 60 μm, 80 μm, 125 μm. The thickness of the hardened functional layer is 3 μm, 4 μm, 5 μm.

[0055] The method of applying the hardening liquid can be a slit coating method, a micro gravure coating method, a doctor blade coating method, a Mayer rod coating method, a roller coating method and a blade coating method to form a coating layer. If the coating method is selected as a micro gravure coating method and a slit coating method, the coating effect can be better.

[0056] After the hardening liquid is applied, the hardening liquid is dried in a manner of: drying for 2 to 4 minutes at an environment of 60 to 80° C. As an example, the temperature of the hardening liquid drying is 60° C., 70° C., 80° C.; and the drying time of the hardening liquid is 2 minutes, 2.2 minutes, 2.5 minutes, 2.8 minutes, or 3 minutes.

[0057] In addition, the embodiment of the present application also provides a vehicle-mounted display device using the above-mentioned hardened film. The hardened film can exert good heat insulation performance and high temperature and high humidity stability in the vehicle-mounted display device.

[0058] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0059] Some of the raw materials used in the following examples and comparative examples are shown in Table 1 below.

[0060] Table 1 Source of raw materials

[0061]

[0062] In the following embodiments, the preparation method of the infrared protection material is as follows:

[0063] (1) Preparation of infrared-proof material R1: Silane coupling agent modified silica sol (referred to as the first modified sol) and tungsten oxide (particle size of 20 nm, infrared blocking rate greater than 99% at a wavelength of 1440 nm) with a mass ratio of 5:1 were mixed and stirred at 1500 rpm for 15 min to obtain the first system. Silane coupling agent modified silica sol (referred to as the second modified sol), isopropyl alcohol and polyether modified polydimethylsiloxane (i.e., polyether siloxane) were added to the first system and stirred and mixed at 1000 rpm for 45 min to obtain infrared-proof material R1.

[0064] The mass ratio of the second modified sol, isopropyl alcohol, polyether-modified polydimethylsiloxane and tungsten oxide is 20:10:0.02:1.

[0065] (2) Preparation of infrared-proof material R2: Aluminum sol modified by silane coupling agent (referred to as the first modified sol) and indium antimony oxide (particle size of 50 nm, infrared blocking rate greater than 99% at a wavelength of 1250 nm) with a mass ratio of 5:1 were mixed and stirred at 1500 rpm for 15 min to obtain the first system. Silane coupling agent modified silica sol (referred to as the second modified sol), isopropyl alcohol and polyether modified polydimethylsiloxane (i.e., polyether siloxane) were added to the first system and stirred and mixed at 1000 rpm for 45 min to obtain infrared-proof material R2.

[0066] The mass ratio of the second modified sol, isopropyl alcohol, polyether-modified polydimethylsiloxane and indium antimony oxide is 20:10:0.02:1.

[0067] Example 1

[0068] This embodiment provides a hardened film, including a PC base film (with a thickness of 125 μm) and a hardened functional layer (with a thickness of 3 μm) attached to the surface of the PC base film. The preparation method of the hardened film includes the following steps:

[0069] (1) Preparation of hardening liquid: According to weight parts, 20 parts of polyether modified polyurethane acrylic resin, 7 parts of dipentaerythritol pentaacrylate, 2.5 parts of infrared protection material R1, 1 part of infrared protection material R2, 1.6 parts of 1-hydroxycyclohexyl phenyl ketone, 20 parts of methyl isobutyl ketone, 10 parts of ethyl acetate, 10 parts of propylene glycol methyl ether and 20 parts of isopropanol were mixed and stirred at 1200 rpm for 120 minutes to obtain a hardening liquid.

[0070] (2) Preparation of hardened film: The hardening liquid is coated on the surface of the PC base film, dried at 80° C. for 2 min, and then subjected to ultraviolet light curing reaction to form a hardened functional layer to obtain a hardened film.

[0071] The preparation methods of Examples 2 to 6 are substantially the same as those of Example 1, the only difference being the types and amounts of the raw materials, as shown in Table 2.

[0072] Table 2 Amount of each component in the hardening solution of Examples 1 to 6 (parts by weight)

[0073]

[0074] Comparative Example 1

[0075] This comparative example provides a hardened film, including a PC base film and a hardened functional layer attached to the surface of the PC base film. The preparation method of the hardened film is substantially the same as that of Example 1, except that:

[0076] In step (1), the infrared protection materials R1 and R2 are not added.

[0077] Comparative Example 2

[0078] This comparative example provides a hardened film, including a PC base film and a hardened functional layer attached to the surface of the PC base film. The preparation method of the hardened film is substantially the same as that of Example 1, except that:

[0079] The infrared protection material R1 in step (1) is replaced by tungsten oxide, and the infrared protection material R2 is replaced by indium antimony oxide, that is, the infrared blocking agent is not subjected to modified nano-sol coating treatment.

[0080] Comparative Example 3

[0081] This comparative example provides a hardened film, including a PC base film and a hardened functional layer attached to the surface of the PC base film. The preparation method of the hardened film is substantially the same as that of Example 1, except that:

[0082] The first modified sol, the infrared blocking agent and the second modified sol are directly added into the hardening solution, that is, step (1) comprises: 20 parts of polyether-modified polyurethane acrylic resin, 7 parts of dipentaerythritol pentaacrylate, 1.9 parts of modified silica sol, 0.5 parts of modified aluminum sol, 0.07 parts of tungsten oxide, 0.03 parts of indium antimony oxide, 0.002 parts of polyether-modified polydimethylsiloxane, 1.6 parts of 1-hydroxycyclohexyl phenyl ketone, and 61 parts of a dispersing solvent (20 parts of methyl isobutyl ketone, 10 parts of ethyl acetate, 10 parts of propylene glycol methyl ether, and 21 parts of isopropanol) are mixed and stirred at 1200 rpm for 120 minutes to obtain a hardening solution.

[0083] Comparative Example 4

[0084] This comparative example provides a hardened film, including a PC base film and a hardened functional layer attached to the surface of the base film. The preparation method of the hardened film is substantially the same as that of Example 1, except that:

[0085] 20 parts of polyether-modified polyurethane acrylic resin were replaced with conventional polyurethane acrylic resin.

[0086] Test example

[0087] The hardened films prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to performance tests, and the test methods were as follows:

[0088] 1. Hardening functional layer thickness test

[0089] The German NXT coating thickness gauge ETA-SST thickness test system is used to measure the thickness of the hardened functional layer of the hardened film using the principle of light diffraction.

[0090] 2. Transmittance / haze

[0091] The transmittance and haze of the cured film were measured by the transmitted light method using a NDH 2000N haze meter manufactured by Nippon Denshoku Co., Ltd. in accordance with JIS K-7105.

[0092] 3.High temperature and high humidity

[0093] After the hardened film was placed in a constant temperature and humidity test chamber at 85°C and 85% RH for 240 hours, it was taken out and allowed to warm up for 2 hours. According to the standard ASTM D-3359, a grid was drawn on the coating surface with a grid knife. After 3M 600 tape was pasted on the drawn grid, the tape was quickly torn off at 180 degrees. The grid shedding condition was observed with a magnifying glass and classified into the following six levels:

[0094] 5B: The coating has not fallen off at all; 4B: The coating has fallen off in an area of ​​<5%; 3B: The coating has fallen off in an area of ​​5% to 15%; 2B: The coating has fallen off in an area of ​​15% to 35%; 1B: The coating has fallen off in an area of ​​35% to 65%; 0B: The coating has fallen off in an area of ​​>65%.

[0095] 4. High temperature / high temperature warping

[0096] (1) High temperature: Place the hardened film in a 105°C oven for 500 hours, then take it out and return it to the temperature for 2 hours. According to standard ASTM D-3359, use a grid knife to draw grids on the coating surface. 3M 600 tape is pasted on the drawn grids, and the tape is quickly torn off in a 180-degree direction. Use a magnifying glass to observe the grid peeling condition, and classify the grid peeling condition into the following six levels:

[0097] 5B: The coating has not fallen off at all; 4B: The coating has fallen off in an area of ​​<5%; 3B: The coating has fallen off in an area of ​​5% to 15%; 2B: The coating has fallen off in an area of ​​15% to 35%; 1B: The coating has fallen off in an area of ​​35% to 65%; 0B: The coating has fallen off in an area of ​​>65%.

[0098] (2) High temperature warpage: Cut the hardened film after the medium and high temperature test in (1) into a 100mm*100mm square, place it with the hardened surface facing up, and measure its side length. When the side length is greater than 90mm, the anti-warpage effect is good.

[0099] 5. Heat insulation (infrared blocking)

[0100] The Agilent carry5000 instrument was used to test the transmittance of the hardened film in each infrared band of 200-2000nm.

[0101] 6. Salt spray resistance

[0102] Using the HYW-90-D fully automatic intelligent salt spray tester from Wuxi Dongpu Instrument Technology Co., Ltd., the surface of the hardened film was sprayed with salt spray for 8 hours and then left to stand for 16 hours. After repeating this for 6 cycles, according to the standard ASTM D-3359, a grid was drawn on the coating surface with a grid knife. After 3M 600 tape was pasted on the drawn grid, the tape was quickly torn off in a 180-degree direction. The grid shedding condition was observed with a magnifying glass, and the grid shedding condition was divided into the following six levels:

[0103] 5B: The coating has not fallen off at all; 4B: The coating has fallen off in an area of ​​<5%; 3B: The coating has fallen off in an area of ​​5% to 15%; 2B: The coating has fallen off in an area of ​​15% to 35%; 1B: The coating has fallen off in an area of ​​35% to 65%; 0B: The coating has fallen off in an area of ​​>65%.

[0104] The above performance test results are shown in Table 3.

[0105] Table 3 Performance test results of hardened film

[0106]

[0107]

[0108] Combining Table 2 and Table 3, it can be seen that the hardened films prepared in Examples 1 to 6 of the present application have good thermal insulation performance and can maintain excellent high temperature and high humidity stability at the same time. The transmittance at a wavelength of 1200nm can be less than 40%, and the adhesion level after high temperature and high humidity treatment can still be maintained at 5B. In addition, the hardened films prepared in Examples 1 to 6 of the present application also have good optical properties, with a transmittance higher than 85% and a haze lower than 1%; as well as good high temperature and salt spray resistance. After high temperature and salt spray treatment, the adhesion can be maintained at 5B; and it can also solve the problem of easy warping of the hardened film after high temperature. The side length of the hardened surface after high temperature treatment is greater than 90mm.

[0109] Figure 2 This is a graph showing the thermal insulation test results of the hardened film provided in Example 1 and Comparative Example 1 of the present application. Figure 2 It can be seen from Table 3 that adding anti-infrared material in the present application can effectively improve the thermal insulation performance of the hardened film.

[0110] By comparing the performance test results of Example 1 and Comparative Example 2, it can be seen that although directly adding infrared blocking agent to the hardening liquid can also improve the thermal insulation performance of the hardened film to a certain extent, after high temperature and high humidity treatment, high temperature and salt spray, the adhesion of the hardened functional layer is significantly reduced, and even peeling and falling off occurs, and the high temperature warping performance is also significantly reduced.

[0111] By comparing the performance test results of Example 1 and Comparative Example 3, it can be seen that although directly adding modified nanosol and infrared blocking agent to the hardening liquid can also give the hardened film good thermal insulation properties, the modified nanosol only plays the role of filler and can only solve the high-temperature warping problem, and cannot effectively wrap the infrared blocking agent to prevent the precipitation of the infrared blocking agent. Therefore, the adhesion after high temperature and humidity, high temperature and salt spray treatment is significantly reduced.

[0112] From the performance test results of Example 1 and Comparative Example 4, it can be seen that the acrylic oligomer with a waterproof group in the curing liquid and the coating of the infrared blocking agent can improve the adhesion to high temperature and high humidity; and when the two exist at the same time, they can not only give the cured film a heat insulation function, but also maintain excellent high temperature, high temperature and high humidity and salt spray resistance stability.

[0113] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A hardening liquid, characterized in that: It includes an acrylate oligomer with a waterproof group, a diluent monomer and an infrared-proof material; wherein the infrared-proof material includes an infrared blocking agent coated with a modified nanosol, and the modified nanosol includes at least one of a nanosol modified by a silane coupling agent or a nanosol modified by an acrylate.

2. The hardening liquid according to claim 1, characterized in that The infrared blocking agent includes at least one of tin oxide, tungsten oxide, antimony tin oxide or indium antimony oxide; And / or, the particle size of the infrared blocking agent is 10 to 100 nm.

3. The hardening solution according to claim 1, characterized in that: The nano sol includes at least one of silica sol, aluminum sol or zirconium sol; And / or, the silane coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane or allyltrimethylsilane; And / or, the acrylate includes at least one of polyacrylate and acrylate monomer.

4. The hardening liquid according to claim 1, characterized in that: The modified nano sol includes a first modified sol and a second modified sol, the infrared blocking agent is located on the surface of the first modified sol, and the second modified sol covers the first modified sol and the infrared blocking agent.

5. The hardening liquid according to claim 1, characterized in that: The acrylic ester oligomer having a waterproof group includes at least one of a polyether-modified polyurethane acrylic resin or a polycarbonate-modified polyurethane acrylic resin; And / or, the diluent monomer includes an acrylate monomer.

6. The hardening solution according to claim 1, characterized in that: The hardening liquid comprises the following components by weight: 5 to 30 parts of acrylic oligomers having waterproof groups, 2 to 8 parts of diluent monomers, 1 to 6 parts of infrared-proof materials, 0.5 to 3 parts of initiators, and 50 to 140 parts of dispersing solvents.

7. A method for preparing a hardening solution as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: The first modified sol is mixed with an infrared blocking agent to obtain a first system; the first system is mixed with a second modified sol, an alcohol solvent and polyether siloxane to obtain an infrared protection material; wherein the first modified sol and the second modified sol each independently include at least one of a silane coupling agent modified nanosol or an acrylate modified nanosol; The acrylic oligomer having a water-repellent group, the diluent monomer, the infrared-proof material, the initiator and the dispersing solvent are mixed to obtain a hardening solution.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the first modified sol to the infrared blocking agent is (5-10):1; And / or, the mass ratio of the second modified sol to the infrared blocking agent is (5-40):

1.

9. A hardened film, characterized in that: The invention comprises a base film and a hardening functional layer attached to the surface of the base film, wherein the hardening functional layer is obtained by coating and light curing the hardening liquid according to any one of claims 1 to 6.

10. A vehicle-mounted display device, characterized in that: It includes the hardened film as claimed in claim 9.